Social Critique after Post-Structuralism: Lessons from Luhmann, Lukács and Simmel - Salem, A. (Sociologija. Mintis ir veiksmas, 2017)
This article examines the views of three highly distinct social theorists – Niklas Luhmann, György Lukács and Georg Simmel – on the issue of modernity and its effects in an attempt to explore not just the considerable differences but also some common ground between them. It is argued that while these thinkers taken together encompass a wide spectrum of political opinion, and also cover a spectrum between technocratic and anti-rationalist views, those who, in various ways, sanction the rise of modernity and those who criticise it are in many ways in agreement about its characteristics. Beyond this the aim is to address the question of what an exchange between these theorists can reveal for the purpose of continuing a project of social criticism, at a time when any such project must take place in a post-structuralist intellectual context in which all knowledge is fundamentally provisional and uncertain. Even in this situation, it is argued, some positive recommendations can be made for such criticism’s continuing role. The article concludes by making the case, in the dialogue opened up between these otherwise diverse theorists, for a more self-reflexive critical writing, one more aware of its own fragility, of the limits of the position from which it speaks, and of how much it is implicated in what it criticises, and outlines the possibilities for a non-essentialist and non-foundationalist approach to social critique.